Perancangan UI/UX Website E-learning Amikom Solo - Brian Adi Bachtiar; Ina Sholihah Widiati; Sri Widiyanti (Institut Teknologi dan Bisnis (ITB) Semarang, 2023)
E-Learning is an approach to developing knowledge, skills and competencies through internet-based means. E-Learning allows materials to be sent to students via the internet. The use of web-based E-Learning is currently widely applied for schools and universities, but for STMIK Amikom Solo still does not have an E-Learning system. The method used in this research is the literature study method which aims to develop the use of E-Learning websites from various journals that have been analyzed and processed by researchers into an Amikom Solo E-Learning website. From the website built, it can be concluded that it can facilitate students and lecturers in learning activities.